2007
DOI: 10.1016/j.neurobiolaging.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional alterations in semantic dementia: A voxel-based MRI and PET study

Abstract: Rare studies have used MRI and voxel based morphometry (VBM) to assess atrophy, and only two PET studies used SPM to examine functional changes in semantic dementia (SD). Our aim was to highlight both morphological and functional abnormalities in a same group of 10 SD patients, in the entire brain, using a "state of the art" methodology (optimized VBM procedure, PET data corrected for partial volume effects and voxel based analyses). We also used an extensive neuropsychological battery. We showed that main alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(100 citation statements)
references
References 78 publications
6
89
3
2
Order By: Relevance
“…77 ALS and FTD patients have been found to present with semantic memory deficits. 47,49,62,105,106 Still in the semantic domain, deficits in linguistic abilities and social communication have been recently reported in ALS patients found with structural and functional temporal lobe changes. 47,90,107,108 Phukan and colleagues 102 found that 14% of non-demented ALS patients presented with cognitive impairment, including language deficits, but without executive dysfunction.…”
Section: Clinical/neuropsychological Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…77 ALS and FTD patients have been found to present with semantic memory deficits. 47,49,62,105,106 Still in the semantic domain, deficits in linguistic abilities and social communication have been recently reported in ALS patients found with structural and functional temporal lobe changes. 47,90,107,108 Phukan and colleagues 102 found that 14% of non-demented ALS patients presented with cognitive impairment, including language deficits, but without executive dysfunction.…”
Section: Clinical/neuropsychological Findingsmentioning
confidence: 98%
“…41,60 In SD, hypometabolism was found in anterior poles, hippocampal region and fusiform gyrus. [61][62][63] Despite specific patterns of atrophy in each of the syndromes, ALS and FTD show many common areas of atrophy. Taken together, these imaging findings support the notion that ALS and FTD overlap in their neural correlates although some regions may be more affected than others in each of the diseases.…”
Section: Functional Imagingmentioning
confidence: 99%
“…By putting both imaging modalities on the same measurement scale (z-scores) and adjusting for difference in resolution between modalities (differential smoothing; 14 method described in the 'Materials and methods' section), it is possible to compare structural and metabolic deficits, as already done in several other studies 15,16 and even in other imaging modalities (AV45 16 ). Such an approach provides a deeper understanding of the different brain alterations and the pathological mechanisms underlying the disease as conducted in Alzheimer's disease (AD), semantic dementia 15 and Korsakoff's syndrome. 17 In AD, two distinct profiles were found: (a) atrophy exceeding hypometabolism in medial temporal lobe and hippocampus and (b) more severe hypometabolism than GM atrophy in posterior associative areas that may have precede structural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological studies reported that lesions in the anterior region caused amnesia of broad categories of knowledge (Mummery et al, 2000;Chan et al, 2001;Desgranges et al, 2007). Other studies using semantic dementia patients commonly reported lesions in the anterior temporal lobe (Davies et al, 2004;Nestor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%